Measurement of sample and plasma properties in solution-cathode glow discharge and effects of organic additives on these properties. Issue 1 (31st July 2015) - Decker, Christian G.; Webb, Michael R.
Abstract : Effects of organic additives on spectroscopic and electrical properties of a solution-cathode glow discharge are measured. Effects of the discharge on sample solutions with and without additives are measured. Abstract : Solution-cathode glow discharge was studied in an attempt to further elucidate the processes involved in the plasma. Spectroscopic and electrical properties were measured with and without the influence of three organic modifiers: formic acid, acetic acid, and ethanol. Degradation products (CO, C2, and CH) of the modifiers were detected in the plasma spectroscopically. Properties of solutions before and after exposure to the discharge were compared. The effects of organic additives on these solution properties were measured. A single, simple mechanism was not consistent with the data, so a multi-part mechanism is proposed for solution and analyte transport into the plasma. Evaporation from the cathode surface, droplet generation, and chemical generation of volatile species may each play a role.